2009
DOI: 10.1007/s12011-009-8457-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc Supplementation on Antioxidant Activity in Young Wrestlers

Abstract: This study aims to examine the effect of zinc supplementation on free-radical formation and antioxidant system in individuals who are actively engaged in wrestling as a sport. The study registered a total of 40 male subjects, of whom 20 were wrestlers and 20 were sedentary individuals. The subjects were equally allocated to four groups: group 1, zinc-supplemented sportsmen group; group 2, sportsmen group without supplementation; group 3, zinc-supplemented sedentary group; group 4, sedentary group without suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 17 publications
2
25
0
3
Order By: Relevance
“…This observation is in agreement with the earlier study demonstrating an increase in serum zinc and GPx activity in volunteers obtaining zinc supplementation (Kara et al, 2010). The observed direct correlation between serum selenium level and GPx activity confi rm earlier data (Luoma et al, 1984;Kim et al, 2011).…”
supporting
confidence: 93%
“…This observation is in agreement with the earlier study demonstrating an increase in serum zinc and GPx activity in volunteers obtaining zinc supplementation (Kara et al, 2010). The observed direct correlation between serum selenium level and GPx activity confi rm earlier data (Luoma et al, 1984;Kim et al, 2011).…”
supporting
confidence: 93%
“…Given the mechanisms of immune responses, it can be argued that tissue injury in the skeletal muscle resulting from exercise paves the way for activation of immune reactions (6). However, previous studies indicated that a cytokine response may be observed even after exercise that is not strenuous (7). The decisive factor distinguishing elevation of cytokines in response to the immune response to infections from the post-exercise elevation of cytokines is the increase observed in tumor necrosis factor-α (TNF-α) levels in inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Введение цинка в организм лаборатор-ных животных, не подверженных ФН, при-водило к статистически значимому повы-шению активности ГПО, что согласуется с полученными ранее данными [9]. Так, в частности, возможный механизм цинк-индуцированного повышения активности ГПО -модуляция уровня селена в организ-ме [12].…”
Section: Influence Of Zinc Administration On Its Tissue Concetration unclassified